Effect of bariatric surgery on adipose tissue distribution in severely obese patients - Dadson, Prince Yaw (fi=Turun yliopisto|en=University of Turku|, 2015)
Background and aim: Bariatric surgery leads to sustain weight loss, improve metabolic and lipids profiles and ultimately leads to remission of type 2 diabetes (T2DM) in some obese individuals. The aim of the project is to evaluate the effect of bariatric on abdominal fat distribution in severely obese T2DM and non-T2DM obese patients. Study design and methods: A total of 23 morbidly obese subjects (mean ± SD body mass index 43.0 ± 3.6 kg/m2, age 46.5 ± 9.0 years) were recruited from the lager multicenter SLEEVEPASS studies (ClinicalTrials.gov/NCT00793143). 10 healthy age-matched non-obese individuals served as controls. The obese patients were studied before and 6 months after surgery. At baseline, there were 9 T2DMs and 14 non-diabetics. After surgery, there were 5 remitters and 4 nonremitters. Whole body magnetic resonance imaging including the abdominal regions was performed for the obese subjects before and 6 months after surgery and for the controls once. Abdominal fat were compartmentalized and analyzed. Results: At 6 months of follow-up, BMI in the obese decreased significantly (from 43 ± 4 to 33 ± 2 kg/m2, p < 0.001) with substantial improvement in whole body insulin sensitivity (from 12.2 ± 5.7 to 23.3 ± 8.1 µmol/kg/min, p < 0.001). Intraperitoneal fat mass decreased by 46% (from 3.4 ± 1.1 to 1.9± 1.0 kg, p < 0.001) more than the rest of the compartments. Abdominal visceral compartments in obese correlated with glycemic status independent of surgery. Pre-surgery posterior deep and intraperitoneal fat mass were better predictors of post-surgery glycemic status in obese. Remitters showed significant improvement in whole body insulin sensitivity (from 9.1 ± 2.1 to 20.9 ± 8.4 µmol/kg/min, p = 0.02), fasting glucose decreased significant only in nonremitters (from 7.1 ± 1.1 to 6.0 ± 0.8 mmol/l, p = 0.05) after surgery. There were no differences in extraperitoneal fat mass in remitters and superficial subcutaneous fat in non-remitters but all other compartments decreased significantly 6 months after the surgery Conclusion: Both deep subcutaneous and visceral fat are important contributors to glycemic status in obese subjects. Whereas visceral fat compartments are directly involved in T2DM, superficial subcutaneous may have offered protection against T2DM in obese subjects.